2020
DOI: 10.1111/mec.15403
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting genomic and phenotypic outcomes of hybridization between pairs of mimetic butterfly taxa across a suture zone

Abstract: Hybrid zones, whereby divergent lineages come into contact and eventually hybridize, can provide insights on the mechanisms involved in population differentiation and reproductive isolation, and ultimately speciation. Suture zones offer the opportunity to compare these processes across multiple species. In this paper we use reduced‐complexity genomic data to compare the genetic and phenotypic structure and hybridization patterns of two mimetic butterfly species, Ithomia salapia and Oleria onega (Nymphalidae: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 101 publications
(136 reference statements)
0
13
0
Order By: Relevance
“…Here we focus on the two closely related taxa, Ithomia salapia aquinia and I. s. derasa. The two subspecies have somewhat divergent wing color patterns (see Supporting Information File 1, Figure S1) [4], are widely distributed, and parapatric in north-eastern Peru [5]. Despite the geographic overlap in distribution, a recent genetic study showed limited gene flow [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we focus on the two closely related taxa, Ithomia salapia aquinia and I. s. derasa. The two subspecies have somewhat divergent wing color patterns (see Supporting Information File 1, Figure S1) [4], are widely distributed, and parapatric in north-eastern Peru [5]. Despite the geographic overlap in distribution, a recent genetic study showed limited gene flow [4].…”
Section: Introductionmentioning
confidence: 99%
“…The two subspecies have somewhat divergent wing color patterns (see Supporting Information File 1, Figure S1) [4], are widely distributed, and parapatric in north-eastern Peru [5]. Despite the geographic overlap in distribution, a recent genetic study showed limited gene flow [4]. Reproductive isolation in mimetic butterflies can be driven by multiple factors, notably non-random mating based on color pattern and/or sexual pheromones [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…While providing interesting results, comparisons using individuals from more natural populations, clades and/or subspecies within the S. trutta complex remain necessary in order to better investigate and elucidate the evolutionary history of trout regarding body colour patterns and to refine the CPL list. DdRADseq used in this study is however a reduced representation sequencing technique targeting only a tiny portion of the genome (∼1%) that is considered either to successfully target (Belsford et al, 2017) or miss important loci responsible for colour and pigmentation patterns (Gauthier et al, 2020). Thus, RNA sequencing or gene expression studies promoted by Djurdjevič et al (2019), together with more standard association studies in control settings that, as for other traits, may provide better estimates of QTL number (if any), variation in effect sizes among loci and more accurately pointing key master genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The two subspecies have somewhat divergent wing color patterns (see Supporting Information, Figure S1) [4], are locally abundant, widely distributed, and are parapatric in north-eastern Peru (San Martin) [5]. Despite the geographic overlap in distribution, a recent genetic study showed limited gene flow [4].…”
Section: Introductionmentioning
confidence: 99%
“…The two subspecies have somewhat divergent wing color patterns (see Supporting Information, Figure S1) [4], are locally abundant, widely distributed, and are parapatric in north-eastern Peru (San Martin) [5]. Despite the geographic overlap in distribution, a recent genetic study showed limited gene flow [4]. Reproductive isolation in mimetic butterflies can be driven by multiple factors, notably non-random mating based on color pattern and/or sexual pheromones [6][7][8].…”
Section: Introductionmentioning
confidence: 99%